Integration Of Sodium Alginate With Bacillus Subtilis As Microbial Composite For Fertilizer Coating Towards Green Agriculture - Charles, Ng Wai Chun (2022)
Coating is a protective material that is applied to an object's surface such as fertilizer for various purposes. In this research, microbial composite film was fabricated by integrating sodium alginate with different mass of Bacillus subtilis. The films were tested on its physical, mechanical, chemical, and microbial properties. Then, study was conducted to improve the conductivity, moisture content and added micronutrient of microbial composite films for plants as supplement. Subsequently, organic goat manures as fertilizers were coated with different layers of microbial composite films coating via different drying techniques. Next, plant growth analysis and soil nutrients analysis were conducted by applying fertilizers of no coating, sodium alginate coating, and microbial composite coating (1-layer coating and 2-layer coating) to the plants to see its effect on the nutrients transfer. Furthermore, mathematical modelling was developed for soil nutrients analysis. It is found that 0.5 g bacterial cell mass from log phase had the most significant effect on the properties of the films. Then, by mixing microbial composite solution with 40 ppm copper ions and 1% glycerol render the highest conductivity to the films which is helpful in plant growth. It is also found that both 30-minutes drying and 24-hour drying technique did not give significant difference on the thickness of films and hence, 30-minutes drying technique was chosen as it saved time and cost in the process.